Receptor-mediated selective autophagy degrades the endoplasmic reticulum and the nucleus - Mochida, Keisuke; Oikawa, Yu; Kimura, Yayoi; Kirisako, Hiromi; Hirano, Hisashi; Ohsumi, Yoshinori; Nakatogawa, Hitoshi (Nature (London), 2015)
In yeast, the novel protein Atg40 is enriched in the cortical and cytoplasmic endoplasmic reticulum (ER), and loads these ER subdomains into autophagosomes to facilitate ER autophagy; Atg39 localizes to the perinuclear ER and induces autophagic sequestration of part of the nucleus, thus ensuring cell survival under nitrogen-deprived conditions. ER-phagy receptors mapped The endoplasmic reticulum (ER) is a complex network of membranes involved in protein and lipid synthesis, ion homeostasis, protein quality control and organelle communication. It is also a source of membrane-bounded vesicles called autophagosomes, the vehicles for the self-digesting cellular process of autophagy. Two papers published online this week [in this issue of Nature] show how the ER itself is targeted for degradation by autophagy — a process that could ensure constant ER turnover in response to cellular requirements. Ivan Dikic and coworkers find the protein FAM134B is an ER-resident receptor that facilitates 'ER-phagy'. Downregulation of this protein — mutations of which can cause sensory neuropathy in humans — resulted in expanded ER structures and degeneration of mouse sensory neurons. Hitoshi Nakatogawa and colleagues show that the same phenomenon is conserved in yeast, where Atg40 is enriched in the cortical and cytoplasmic ER, loading these ER subdomains into autophagosomes. A further ER-phagy receptor, Atg39, localizes to the perinuclear ER (or the nuclear envelope) and induces autophagic sequestration of a part of the nucleus, thus ensuring cell survival under nitrogen-deprived conditions. Macroautophagy (hereafter referred to as autophagy) degrades various intracellular constituents to regulate a wide range of cellular functions, and is also closely linked to several human diseases 1 , 2 . In selective autophagy, receptor proteins recognize degradation targets and direct their sequestration by double-membrane vesicles called autophagosomes, which transport them into lysosomes or vacuoles 3 . Although recent studies have shown that selective autophagy is involved in quality/quantity control of some organelles, including mitochondria and peroxisomes 4 , it remains unclear how extensively it contributes to cellular organelle homeostasis. Here we describe selective autophagy of the endoplasmic reticulum (ER) and nucleus in the yeast Saccharomyces cerevisiae . We identify two novel proteins, Atg39 and Atg40, as receptors specific to these pathways. Atg39 localizes to the perinuclear ER (or the nuclear envelope) and induces autophagic sequestration of part of the nucleus. Atg40 is enriched in the cortical and cytoplasmic ER, and loads these ER subdomains into autophagosomes. Atg39-dependent autophagy of the perinuclear ER/nucleus is required for cell survival under nitrogen-deprivation conditions. Atg40 is probably the functional counterpart of FAM134B, an autophagy receptor for the ER in mammals that has been implicated in sensory neuropathy 5 . Our results provide fundamental insight into the pathophysiological roles and mechanisms of ‘ER-phagy’ and ‘nucleophagy’ in other organisms.